2009
DOI: 10.1161/strokeaha.108.540997
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Mental Imagery Augment Generalization of Learning in Acute Poststroke Patients

Abstract: Background and Purpose-Our previous studies demonstrated that mental imagery intervention enhanced poststroke patients relearning daily task performance. This study aimed to test the efficacy of mental imagery for promoting generalization of the task skills learned in a training environment to trained and untrained tasks carried out in a novel environment. Methods-Thirty-five acute poststroke patients were randomly assigned to the mental imagery (MI; nϭ18) or conventional functional rehabilitation (FR; nϭ17) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 11 publications
2
85
0
3
Order By: Relevance
“…125,132,717 Mental practice, or mental imagery, may be useful as an adjunct to upper extremity exercise therapies. [718][719][720][721][722] Initial training in mental practice occurs within a therapy session, but additional practice can happen outside formal therapy time. It is feasible to integrate mental practice with physical practice.…”
Section: Iib Bmentioning
confidence: 99%
“…125,132,717 Mental practice, or mental imagery, may be useful as an adjunct to upper extremity exercise therapies. [718][719][720][721][722] Initial training in mental practice occurs within a therapy session, but additional practice can happen outside formal therapy time. It is feasible to integrate mental practice with physical practice.…”
Section: Iib Bmentioning
confidence: 99%
“…Although several studies have reported positive findings [10][11][12] , a recent large, randomized, controlled trial in subacute stroke patients reported no significant clinical improvement of MI practice as add-on therapy to standard treatment or compared with mental practice without motor content 13 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5,[7][8][9][10][11]15,16,22,27,33,38 Physical practice of the task was done prior to motor imagery in nine studies 4,[7][8][9][10][11]19,29,33 or was alternated with motor imagery in 15 studies. [12][13][14]16,20,21,24,25,28,30,32,35,37,39,40 One neglect study used physical practice of the unaffected arm. 42 The other neglect and all the pain studies did not use any physical practice.…”
Section: Resultsmentioning
confidence: 99%